Characterization of mucin – lipid droplet interactions: Influence on potential fate of fish oil-in-water emulsions under simulated gastrointestinal conditions. (May 2016) - Chang, Yaoguang; McClements, David Julian
Abstract: The influence of mucin upon the properties and stability of oil-in-water emulsions containing lipid droplets coated by either a protein (caseinate) or non-ionic surfactant (Tween 80) was studied. At pH values below the isoelectric point of emulsion ( e.g ., stomach conditions), anionic mucin molecules bound to the surfaces of cationic caseinate-coated lipid droplets, which led to extensive bridging flocculation and droplet coalescence. Conversely, at pH values above the isoelectric point ( e.g ., mouth conditions), there was an electrostatic repulsion between anionic mucin molecules and anionic caseinate-coated lipid droplets. At this pH, relatively high levels of mucin promoted droplet flocculation through a depletion mechanism. The extent of droplet flocculation and/or coalescence in the systems depended on both the droplet and mucin concentration. Emulsions stabilized by the non-ionic surfactant were not susceptible to bridging flocculation, and only exhibited depletion flocculation at high mucin levels, which was attributed to the strong steric repulsion between them. These results have important implications for understanding the gastrointestinal fate of lipid droplets, which is critical for the development of foods with improved nutritional attributes. Graphical abstract: Highlights: Interactions between mucin and fish oil droplets were systematically characterized. The interactions depended on emulsifier type, pH, droplet and mucin concentrations. Caseinate-coated emulsion with mucin was susceptible to flocculation and coalescence. It showed bridging at pH 2.5 (pH in stomach), and depletion at pH 6.8 (pH in mouth). Tween 80-coated emulsion only exhibited depletion at pH 6.8 and high mucin levels.